Pastoraat as vertolking: Metaforiese teologie binne die konteks van "n pastorale hermeneutiek - Louw, D. J. (Hervormde teologiese studies, 1999)
Pastoral care as hermeneutics: The function of metaphorical theology regarding pastoral counseling. A hermeneutics of pastoral care should be viewed as a theological issue. Hence the importance of God-language and the naming of God in pastoral care. The underlying assumption is that inappropriate images of God have a hampering effect on faith experiences. It is, therefore, impotant that a hermeneutics of pastoral care should probe into the meaning dimension of God-images in order to instil hope and foster spirituality. Four biblical metaphors are discussed: shephtrd, servant, paraclete and wisdom. Our choice, within the context of postmodernity, is for the metaphor "God as Friend". It conveys not only the compassion of God, but also the covenantal intimacy and faithfulness of God (God as a "Soul Friend" within "koinonia").